Obstacles for History Teachers in Implementing the 2013 Curriculum in Public High Schools in Mranggen District - Munandar, Muhammad Eko Aris (Indonesian Journal of History Education, 2019)
Curriculum 2013 is a new curriculum that was developed from the KTSP curriculum. To implement Curriculum 2013, teachers have to face problems. The objectives of this research are to know the understanding of history teachers for curriculum 2013, the issues which the teachers face, and the way of history teachers to overcome the difficulties in curriculum 2013 to SMA N in Mranggen. To collect data, the researcher used observation, interviews, and documentation. The object of this research is history teachers. The researcher chose SMA N 1 Mranggen and SMA N 2 Mranggen to do the research. The results of this research show that the understanding of history teachers in SMA N of sub-district Mranggen has been good; however, there are some problems faced in teaching process, and history teachers have their way to overcome the difficulties in teaching process.